2018
DOI: 10.3389/fnins.2018.00878
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency rTMS of the Primary Motor Area Does Not Modify the Response of the Cerebral Cortex to Phasic Nociceptive Stimuli

Abstract: Repetitive transcranial magnetic stimulation (rTMS) is a non-invasive technique of cortical stimulation. Although the exact mechanism of action is not clearly understood, it has been postulated that rTMS action on pain depends most on stimulation sites and stimulation parameters. Most studies concern high-frequency rTMS of the primary motor cortex (M1). High-frequency rTMS over motor cortex seems to induce an analgesic effect while contrasting results were reported after low-frequency rTMS. The aim of the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Other studies used low-frequency rTMS to modify the operation of various lateral networks in the prefrontal cortex (35). In other studies, different lateral networks in the frontal cortex were differentially affected by low-frequency rTMS (36). Fecteau found that the 1-Hz rTMS can improve naming skills in individuals with ASD (37).…”
Section: Rtms Could Acted As An Investigational Tool In Asdmentioning
confidence: 99%
“…Other studies used low-frequency rTMS to modify the operation of various lateral networks in the prefrontal cortex (35). In other studies, different lateral networks in the frontal cortex were differentially affected by low-frequency rTMS (36). Fecteau found that the 1-Hz rTMS can improve naming skills in individuals with ASD (37).…”
Section: Rtms Could Acted As An Investigational Tool In Asdmentioning
confidence: 99%
“…Traditionally, low-frequency (LF) rTMS (defined as stimulation at frequencies below 1 Hz) has been shown to reduce cortical excitability, whereas high-frequency (HF) rTMS (stimulation at frequencies over 1 Hz) has the opposite effect (Wassermann, 1998;Wagner et al, 2007;Bai et al, 2022). Multiple studies have shown that HF-rTMS provides better pain relief than LF stimulation (Cruccu et al, 2007;Borckardt et al, 2011;Pazzaglia et al, 2018). In previous studies on the analgesic effect of rTMS on PSP, HF-rTMS (5-20 Hz) was found to be effective in relieving pain in PSP.…”
Section: E Ect Of Rtms On Pspmentioning
confidence: 99%
“…Traditionally, low-frequency (LF) rTMS, defined as stimulation below 1 Hz, has been shown to reduce cortical excitability, whereas high-frequency (HF) rTMS, with frequencies above 1 Hz, exerts the opposite effect (Cruccu et al, 2007 ; Bai et al, 2022 ). Previous studies investigating the analgesic effects of rTMS on PSP have discovered that HF-rTMS (5–20 Hz) can effectively alleviate PSP-related pain (Pazzaglia et al, 2018 ). Compared to single and short-term interventions, multiple sessions and longer durations of intervention have been found to produce superior analgesic outcomes (Hosomi et al, 2013 ; Ramger et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%